Physicochemical and organoleptic evaluation of muffin partially substituted with roselle calyces (Hibiscus sabdariffa. L) powder - Siti Faridah Mohd. Amin; Hasmadi Mamat; Lee, Jau-Shya; Nurul Syuhada Roslan (Universiti Malaysia Sabah, 2014)
The effect of substitution of wheat flour with 0%, 5%, 10%, 15% and 20% roselle calyces powder (RCP) on the physicochemical and sensory characteristics of muffin was studied. Roselle calyces powder was produced by using spray drying. The physical (weight, loaf volume, specific volume and oven spring) and proximate analysis showed significant difference (p<0.05) between control and muffin substituted with RCP. Increasing the level of substitution from 5% to 20% of RCP significantly (p<0.05) increased the ash and crude fiber content in muffin samples. Sensory evaluation results indicated that muffin with 10% substitution of RCP was rated the most acceptable.